The development and evaluation of a vaccination pathway for children with intellectual and developmental disability and needle fear - Natalie Ong; Deidre Brogan; Abbie Lucien; Shayna Wolman; Denise Campbell; Lucy Deng; Archana Koirala; Pankaj Garg; Ketaki Sharma (Wiley, 2024)
Abstract This qualitative study describes the development and evaluation of a clinical pathway to facilitate the implementation of catch‐up vaccinations for children with significant needle fear, particularly in children with developmental disabilities. The Specialist Immunization Team, based at a tertiary level teaching children's hospital, participated in process mapping activities using Motivational Interviewing (MI) techniques and reflective discussions. Team members developed a clinical pathway by incorporating parental feedback from semistructured interviews and clinical expertise from within the team, facilitated by colleagues from the Child Development Unit. A process map was developed that included process strengths and touch points with an action plan that was discussed and agreed upon. A repeat process mapping activity was conducted 16 months later. Reports from parental feedback included: positive, efficient, and successful experiences of having their child undergo catch‐up vaccinations. The experience empowered families for further procedures. Team members reported improvements in triaging appropriate children for the pathway, and an increase in confidence to interact and manage behaviors of children with significant anxiety and challenging behaviors. They also reported an increase in successful vaccinations with improved clinical judgment of facilitating the sedation pathway. This study demonstrates that using group facilitation using motivational interviewing in reflective discussions and process mapping utilizing parent and staff feedback in service improvement activities results in efficient and successful service delivery with improved patient outcomes.